PSEUDOSINHALITE IS A STRUCTURAL ISOTYPE OF CHONDRODITE - Strunz H.; Nickel H.H. (My University, 2000)
Pseudosinhalite, Mg2Al3[O|OH|(BO4)2] and chondrodite, Mg5[(F,OH)2|(SiO4)2] are shown to be isostructural. Compositional and crystallographic relationships between members of the forsterite-clinohumite polysomatic series and their borate isotypes are demonstrated.